Is a proton-pump inhibitor necessary after endoscopic submucosal dissection for superficial esophageal neoplasms? A propensity score analysis. (November 2020) - Kanaoka, Hideaki; Iwatsubo, Taro; Takeuchi, Toshihisa; Kojima, Yuichi; Takahashi, Yoshiaki; Hakoda, Akitoshi; Nishida, Shinya; Kawaguchi, Shinpei; Ota, Kazuhiro; Shiba, Masatsugu; Higuchi, Kazuhide
Background: Little is known about the efficacy of proton-pump inhibitor (PPI) therapy in the management of esophageal ulcers after endoscopic submucosal dissection (ESD). Therefore, the objective of this study was to investigate the efficacy of PPI in ulcer healing following ESD for superficial esophageal neoplasms, using a propensity score analytic approach. Methods: This retrospective cohort study was conducted at a single referral center. Between April 2005 and August 2015, 199 consecutive patients with superficial esophageal cancer and esophageal dysplasia underwent ESD. For patients with PPI administration, intravenous PPI therapy was commenced immediately after ESD, and oral PPI was administered daily from post-operative day 3, until ulcer healing was identified. We compared the remnant-ulcer rate at 4 weeks after esophageal ESD between the PPI administration and non-PPI groups, using propensity scores and the inverse probability of treatment weighting (IPTW) method. Results: After exclusions, a total of 88 patients were analyzed. The remnant-ulcer rate at 4 weeks after ESD was 25.5% (12/47) and 14.6% (6/41) in the PPI administration and non-PPI groups ( p = 0.21). After adjusting for background factors using IPTW, the risk of a remnant ulcer in the PPI administration group was not decreased significantly compared with that in the non-PPI group [odds ratio (OR) = 2.42, 95% confidence interval (CI): 0.73–7.97, p = 0.15]. Furthermore, PPI therapy did not decrease significantly the remnant-ulcer rate on logistic regression analysis after adjusting for the propensity score (OR = 2.40, 95% CI: 0.69–8.32, p = 0.15). Conclusion: PPI administration does not promote ulcer healing after ESD for superficial esophageal squamous cell carcinoma.